Spectrally resolved radiative observations of the Earth in the Far-Infrared using the Tropospheric Airborne Fourier Transform Spectrometer (TAFTS) - Murray,JE; Pickering,JC; Brindley,H; Fox,S; Ade,P; Tucker,C; Fox,C; Harlow,C; Last,A (2018)
The Far-Infrared contributes up to 50% of the radiative emission from Earth to space, however, FIR observations are lacking. Satellite instruments are proposed or set for deployment, we discuss the practicalities of supporting these missions with TAFTS.